The role of emotional intelligence in improving the quality of employee interaction and its impact on customer satisfaction with work-life balance as a moderation variable - Tritami, Devita; Suhardi, Suhardi; Yani, Ahmad (International Journal of Applied Finance and Business Studies, 2025)
This research endeavors to investigate the significance of emotional intelligence in enhancing the quality of employee interactions and its subsequent influence on customer satisfaction, while considering work-life balance as a moderating variable. Emotional intelligence is pivotal in fostering constructive interactions between employees and customers, which may ultimately facilitate an enhancement in customer satisfaction. Nevertheless, work-life balance may serve as a moderating factor in this association, wherein employees who experience a favorable work-life balance are generally more adept at regulating their emotions and delivering superior service quality. This study employs a quantitative methodology, utilizing data collected through the administration of questionnaires. The research sample comprised 200 respondents employed within the customer service sector. Data analysis was conducted utilizing moderation regression techniques to examine the interrelationships among the variables under investigation. The findings of the study indicated that emotional intelligence exerted a significant impact on the quality of employee interactions, yet did not demonstrate a direct influence on work-life balance. Furthermore, the quality of employee interaction significantly affected both work-life balance and customer satisfaction, thereby underscoring the critical importance of positive interactions for organizational success. Work-life balance was found to exert a beneficial influence on customer satisfaction, necessitating that corporations prioritize employee well-being. Management must formulate policies that endorse work-life balance and simultaneously enhance employee communication skills to elevate customer satisfaction.